Beam-switching-assisted CMA initialization for handset adaptive antenna - Boonpoonga, Akkarat; Sirisuk, Phaophak; Phongcharoenpanich, Chuwong; Krairiksh, Monai (My University, 2007)
This paper presents two initialization schemes: phased array-assisted initialization and switched-beam element phased array-assisted initialization, for a constant modulus algorithm (CMA). Both techniques utilize a beam with maximum received power obtained by beam-switching of array antenna to initial CMA. The techniques can significantly improve convergence properties of CMA, which is employed for weight adjustment of an adaptive antenna system. The architecture of the proposed adaptive antenna system is illustrated to show the low-cost assistance for CMA initialization. Finally, simulation results are shown to evaluate SINR performance of the proposed techniques. ©2007 IEEE.
Keywords: Adaptive antenna; CMA; Phased array antenna